Membangun Jiwa Patriotisme Melalui Pendidikan Kewarganegaraan Bagi Generasi Muda - Atika Fitriani; Cindy Fredicia Putri; Putri Dasti S Harahap; Ilham Hudi (International Forum of Researchers and Lecturers, 2024)
One concept of education known as civic education aims to educate young people to become citizens with character. The purpose of this education is to teach young people to think critically about national and international issues so that they can make changes to improve the condition of Indonesia, and show that civic education can build young people who have a sense of nationalism, love for the country, and tolerance. This research uses qualitative methodology to analyze literature and descriptive data to show how important civic education is to build responsible and honest characters. The research shows that civic education includes an understanding of the political and legal system as well as instilling positive attitudes, values and morals in everyone. It is expected that the next generation has a strong personality and can contribute positively to society. Therefore, this study emphasizes how important civic education is in preparing individuals to become active, responsible citizens and play a role in building an inclusive and democratic societ